1977
DOI: 10.1126/science.847477
|View full text |Cite
|
Sign up to set email alerts
|

Antischizophrenic Drugs: Chronic Treatment Elevates Dopamine Receptor Binding in Brain

Abstract: Chronic treatment of rats with the neuroleptic drugs haloperidol, fluphenazine, and reserpine elicits a 20 to 25% increase in striatal dopamine receptor binding assayed with [3H]haloperidol. This increase in receptor sites may account for behavioral supersensitivity to dopamine receptor stimulants in such animals and for tardive dyskinesia in patients treated with these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
184
1
3

Year Published

1978
1978
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,003 publications
(205 citation statements)
references
References 16 publications
16
184
1
3
Order By: Relevance
“…On the basis that clinical records typically demonstrate a varied dosing regimen for schizophrenic patients, it was also important to confirm that D2 receptor Kd levels were also elevated as compared to controls, offering indirect evidence of the presence of residual neuroleptics (Figure 1). Finally, D2 receptor levels, measured with 3H-raclopride, were also found to be elevated in schizophrenics, offering additional support for the handful of studies that have addressed this question (Burt et al 1977;Mackay et al 1982) and suggested that this results from neuroleptic treatment (Figure 1).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…On the basis that clinical records typically demonstrate a varied dosing regimen for schizophrenic patients, it was also important to confirm that D2 receptor Kd levels were also elevated as compared to controls, offering indirect evidence of the presence of residual neuroleptics (Figure 1). Finally, D2 receptor levels, measured with 3H-raclopride, were also found to be elevated in schizophrenics, offering additional support for the handful of studies that have addressed this question (Burt et al 1977;Mackay et al 1982) and suggested that this results from neuroleptic treatment (Figure 1).…”
Section: Resultsmentioning
confidence: 75%
“…To our knowledge, this is the first time that elevated D2 binding has been shown to be detrimentally associated with a behavioral parameter. Although the elevation of dopamine receptors by neuroleptics is well established (Mackay et al 1982), the behavioral consequences have been more difficult to define (Burt et al 1977). In this regard, the main focus has been on such extrapyramidal disturbances as tardive dyskinesia, which are assumed to result from chronic neuroleptic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Increased dopamine sensitivity manifests rapidly in animals receiving dopamineblocking agents (Tarsy and Baldessarini 1974;Gianutsos and Moore 1977;Burt et al 1977). In contrast, TD rarely appears without a considerably longer period of neuroleptic exposure (Jimenez-Jimenez et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that TD is related to increased receptor binding sensitivity in the basal ganglia, stemming from long-term D 2 receptor blockade by neuroleptics (Klawans 1973). Administration of D 2 blocking agents induces an increase in striatal D 2 receptor density (Burt et al 1977;Clow et al 1979;Owen et al 1980) and dopamine turnover in rodents (Clow et al 1978(Clow et al , 1979, as well as an increase in D 2 re-ceptor sensitivity to indirect dopamine agonists (Tarsy and Baldessarini 1974;Gianutsos and Moore 1977;Clow et al 1978Clow et al , 1979Owen et al 1980). Clinical observations also support suggestions that neurolepticrelated increases in D 2 binding sensitivity may be involved in TD.…”
mentioning
confidence: 99%
“…This dosage schedule and duration of drug treatment has been shown to be sufficient to induce DA cell depolarization block (Bunney and Grace, 1978;Chiodo and Bunney, 1983;White and Wang, 1983). Furthermore, to determine whether any alterations may correlate with the induction of DA receptor supersensitivity during APD treatment, the assessments were also carried out in rats that had been treated with haloperidol for 2 weeks, which is sufficient to cause DA receptor supersensitivity in the dorsal striatum (Burt et al, 1977;Muller and Seeman, 1978;Bannon et al, 1980) without inducing DA cell depolarization block (Chiodo and Bunney, 1983;White and Wang, 1983). Two dimensions of drug action were assessed: (1) their effect on the incidence and extent of dye coupling, and 2) their selectivity for neurons in the calbindin-positive motor regions (e.g., striatal matrix and accumbens core regions) or the calbindin-negative limbit regions (i.e., striatal patch and accumbens shell regions) of the striatal complex.…”
mentioning
confidence: 99%